MANAJEMEN WEBSITE DI MA NEGERI 2 SURAKARTA SEBAGAI MEDIA INFORMASI DAN PROMOSI - Nisa, Shifa Khairun; Hidayah, Nurul (Universitas Islam Negeri Sumatera Utara Medan, 2022)
AbstractThis study aims to determine whether the MAN 2 Surakarta website is used as a medium of information and promotion. The method used in this research is qualitative research. This research was carried out in October 2022. Data collection was carried out by interviews and observations. How to examine it by observing the MAN 2 Surakarta website media and conducting direct interviews with relevant sources. Then look at several sources from the MAN 2 Surakarta website. The validity of the data in this study used source triangulation and technique triangulation. The sample used in this study is the MAN 2 Surakarta website. According to the research results, at MAN 2 Surakarta, it shows that the website used functions as an information and promotional medium. If schools ignore media websites, they will lose students. Schools need to use website marketing principles to attract parents of students to want to send their children to these institutions.